CLASSROOM TO CUBICLE: HITTING THE GROUND RUNNING IN THE REAL WORLD OF SOFTWARE DEVELOPMENT. - Slocum, Mary (InSight: Rivier Academic Journal, 2011)
Computer science classes help students become good programmers. But, does it take more to be successful when starting your first job after graduating? There are other areas that computer science undergraduates need to be familiar with before entering the technical work force. This is intended to provide graduates with an edge: an inside look at the roles, processes, and project workflow to enable students to adjust to the workplace and become productive quickly.